ANALYSIS OF HEALTHCARE QUALITY IN THE ERA OF DIGITALIZATION: CHALLENGES AND OPPORTUNITIES - Viegas, Inacio Sarmento (International Journal of Social Service and Research, 2024)
Digitalization offers numerous opportunities to improve the quality of health services. This study aims to analyze the impact of digitalization on the health services, identify the challenges faced in the implementation of digital technology, and explore the opportunities offered by digitalization in improving the health service quality. A qualitative approach is used to understand the perspectives and experiences of patients and medical personnel towards digitalization. Quantitative analysis is carried out using descriptive and inferential statistics to identify trends and patterns in the data. Thematic analysis techniques are used to identify the main themes and categories that emerged from the interview and observation data. Digitalization has a significant impact on the quality services, both positive and negative. To maximize the benefits of the digitalization, efforts are needed to address existing challenges, including increasing access to digital technology and strengthening data security and privacy, and providing training and support for medical personnel. Further research is needed to explore how digital technology can be used to improve health services and provide recommendations to overcome existing challenges.